Shifting Cultivation in North Eastern Hills Region: An Over View - Satapathy, K.K. (Journal of Soil and Water Conservation, 2022)
The paper takes an overview of the problem of shifting cultivation practised by the tribal people in the hilly terrains of North Eastern India. This primitive agriculture developed in an ecosystem providing little alternative is a predatory system of agriculture involving indiscriminate cutting and burning of forests improper land use leading to resource degradation, ecological imbalances as well as adverse socio-economic effects. The variety of schemes currently undertaken by the Government to control it are not so large to make a dent on the overall problem; their impact in respect of weaning the people away from the shifting cultivation is yet to be assessed However, it has been established that a three dimensional approach- development of agriculture jorestry and animal husbandry- coupled with the provision of variety of civic ammenities is an effective strategy to induce the tribal people to switch over from shifting cultivation to a permanent one. The multi- disciplinary research programme of .ICA R has identified several viable watershed based mixed land use farming systems which, alongwith appropriate soil conservation measures, has the scope of using the steep hill slopes for crop production bringing down the soil loss on per with forest areas.